Molecular systematics of the fishfly genus Anachauliodes Kimmins, 1954 (Megaloptera: Corydalidae: Chauliodinae) - Yue, Lu; Liu, Xingyue; Hayashi, Fumio; Wang, Mengqing; Yang, Ding (Zootaxa, 2015)
The fishfly genus Anachauliodes Kimmins, 1954 is endemic to the Oriental region and currently includes two species, Anachauliodes tonkinicus Kimmins, 1954 and A. sinensis Yang & Yang, 1992. These species are similar morphologically. We sequenced three mitochondrial genes: COI, ND2 and 16S rRNA in order to clarify the specific identity of these two species. Our results do not support the separation of these two species. We were also not able to find any morphological characters during comparison of Anachauliodes specimens from various localities useful in distinguishing these two species. Based on these results, we synonymize A. tonkinicus and A. sinensis and recognize A. laboissierei (Navás, 1913), comb. nov. & stat. rev. as the only valid species of Anachauliodes.